Addressing Disability in a Healing and Reconciling Community - Kabue, Samuel (Journal of religion, disability & health, 2006)
A keynote address delivered at the Conference on World Mission and Evangelism, Come Holy Spirit: Heal and Reconcile, Called by Christ to be Reconciling and Healing Communities. Athens, Greece, May 11, 2005. This presentation is made within the overall theme of the Conference on World Mission and Evangelism, which is “Called in Christ to be reconciling and healing communities.” The emphasis of the plenary is on “community” and the way community life may or may not have healing and reconciling quality and effect. I have attempted to explore this in the light of persons with disabilities in the contemporary church and society.